IMPLEMENTASI PELATIHAN KEYBOARD DASAR BAGI REMAJA DI GEREJA HKI PADANG MENGKUDU - Helen Yohana Sinaga; Testi Bazarni Zebua; Novita Aditya Manalu; Aprinaldi Patiaraja Simarangkir; Lince Rauli Ture Simamora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of basic keyboard training for adolescents at Huria Kristen Indonesia (HKI) Padang Mengkudu Church. The background stems from the limited number of church music servants, who rely solely on one player, necessitating development and regeneration through music training for adolescents. The research employs a qualitative approach with a descriptive method. Subjects include music experts, church music servants, and adolescent training participants. Data collection was conducted through observation, interviews, and documentation. Data analysis involved stages of reduction, presentation, and verification. The findings reveal that the basic keyboard training was carried out in a structured and gradual manner over 16 sessions, scheduled four times a week. The materials covered instrument introduction, key-playing techniques, reading numeric notation from the Buku Ende book, basic chord exercises, and coordination between both hands. This training provided initial music experience for novice adolescents who had never played the keyboard before, equipping them with fundamental skills to perform simple songs in the church setting. Therefore, the implementation of basic keyboard training at HKI Padang Mengkudu Church proceeded smoothly and made a positive contribution to adolescent development and the sustainability of church music ministry.